2011
DOI: 10.1007/s11306-011-0302-7
|View full text |Cite
|
Sign up to set email alerts
|

Urine metabolite profiling offers potential early diagnosis of oral cancer

Abstract: Abstract:Oral cancer is the sixth most common human cancer, with a high morbidity rate and an overall 5-year survival rate of less than 50%. It is often not diagnosed until it has reached an advanced stage. Therefore, an early diagnostic and stratification strategy is of great importance for oral cancer. In the current study, urine samples of patients with oral squamous cell carcinoma (OSCC, n = 37), oral leukoplakia (OLK, n = 32) and healthy subjects (n = 34) were analyzed by gas chromatography-mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 32 publications
1
29
0
1
Order By: Relevance
“…Urinary metabolomics has been shown to be a powerful screening approach to separate diseased individuals from controls, e.g. in Barrett's oesophagus and oesophageal carcinoma 30, or in separating oral squamous cell carcinomas from oral leukoplakia patients and control groups 31. However, neither of those studies included a separate validation cohort, leaving open the possibility of co-incidence in the models generated.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary metabolomics has been shown to be a powerful screening approach to separate diseased individuals from controls, e.g. in Barrett's oesophagus and oesophageal carcinoma 30, or in separating oral squamous cell carcinomas from oral leukoplakia patients and control groups 31. However, neither of those studies included a separate validation cohort, leaving open the possibility of co-incidence in the models generated.…”
Section: Discussionmentioning
confidence: 99%
“…From patient urine samples, Xie and colleagues identified a panel of differentially expressed metabolites and demonstrated their utility by logistic regression (LR) modeling (Xie et al, 2012; Table 1). When two metabolites, valine and 6-hydroxynicotic acid, were inputted together in the LR prediction model,the authors were able to identify OSCC with a 98.9% accuracy, and a greater than 90% sensitivity, specificity and positive predictive value (Xie et al, 2012). However, similar to saliva and blood metabolomics, the use of urine samples for HNC metabolomics will require further validation through more independent studies.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that metabolomics approach may complement with the clinical detection of OSCC. 32,33 In this study, we have demonstrated a highly efficient Cap IC-MS method for untargeted metabolomics analysis of head and neck cancer cells and stem-like cancer cells. By comparing the metabolomics profiles of oral stem-like cancer cells (CSCs) to nonstem cancer cells (NSCCs), we found the CSCs have a distinct metabolic phenotype from NSCCs.…”
mentioning
confidence: 99%